2019
DOI: 10.1016/s0140-6736(18)32593-5
|View full text |Cite|
|
Sign up to set email alerts
|

Chlorhexidine versus routine bathing to prevent multidrug-resistant organisms and all-cause bloodstream infections in general medical and surgical units (ABATE Infection trial): a cluster-randomised trial

Abstract: Contributors SSH contributed to study design, study conduct, data analysis, data interpretation and manuscript drafting. RP contributed to study design, study conduct, data interpretation, and manuscript review. KK contributed to study design, data analysis, data interpretation, analytic plan draft, and manuscript review. ES, JM, MH, and RAW contributed to study conduct, data interpretation, and manuscript review. JH, LH, and AG contributed to study conduct, data collection, and manuscript review. KH, LS, REK,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 39 publications
(44 reference statements)
2
66
1
3
Order By: Relevance
“…Daily chlorhexidine bathing has been demonstrated to reduce CLABSI rates among adult and children in intensive care units (Frost et al, 2016;Dicks et al, 2016). Huang et al (2019), despite a lack of overall protective effect in non-ICU patients, found reductions in MRSA and VRE infections in patients with medical devices. 2.…”
Section: Dressing Changesmentioning
confidence: 99%
“…Daily chlorhexidine bathing has been demonstrated to reduce CLABSI rates among adult and children in intensive care units (Frost et al, 2016;Dicks et al, 2016). Huang et al (2019), despite a lack of overall protective effect in non-ICU patients, found reductions in MRSA and VRE infections in patients with medical devices. 2.…”
Section: Dressing Changesmentioning
confidence: 99%
“…Daily bathing or treatment of hospitalized patients with the broad-spectrum antiseptic chlorhexidine gluconate (CHG) has been shown to reduce healthcare-associated bloodstream infections [5][6][7] and colonization by multidrug resistant organisms, particularly in the intensive care unit (ICU) [5]. Extending this treatment outside the ICU may have benefit as well, particularly for patients with medical devices, such as central lines, midline catheters and lumbar drains [8]. However, there is considerable variation in the implementation of CHG treatment when deployed outside the ICU.…”
Section: Introductionmentioning
confidence: 99%
“…It remains one of the most common drug-resistant pathogens that causes infection in hospitalized patients 1,2 . Investments in infection reduction have been posed in intensive care units, which has been de ned as an "epicenter" of nosocomial infections, by measurements of skin decolonization involving daily chlorhexidine bathing 3 . The practice was adopted because of evidence that universal decolonization reduces device-associated bacteremia, all-cause bacteremia, and multidrugresistant organisms 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Investments in infection reduction have been posed in intensive care units, which has been de ned as an "epicenter" of nosocomial infections, by measurements of skin decolonization involving daily chlorhexidine bathing 3 . The practice was adopted because of evidence that universal decolonization reduces device-associated bacteremia, all-cause bacteremia, and multidrugresistant organisms 3,4 . However, the nasal carriage is also unavoidable for endogenous infections and for transmission to other individuals, as the colonization of extra nasal sites often originates from the nasal reservoir 5 .…”
Section: Introductionmentioning
confidence: 99%